The SWI/SNF ATP-dependent nucleosome remodeler promotes resection initiation at a DNA double-strand break in yeast - Wiest, Nathaniel E. (Nucleic Acids Res, 2017)
DNA double-strand breaks (DSBs) are repaired by either the non-homologous end joining (NHEJ) or homologous recombination (HR) pathway. Pathway choice is determined by the generation of 3΄ single-strand DNA overhangs at the break that are initiated by the action of the Mre11–Rad50–Xrs2 (MRX) complex to direct repair toward HR. DSB repair occurs in the context of chromatin, and multiple chromatin regulators have been shown to play important roles in the repair process. We have investigated the role of the SWI/SNF ATP-dependent nucleosome-remodeling complex in the repair of a defined DNA DSB. SWI/SNF was previously shown to regulate presynaptic events in HR, but its function in these events is unknown. We find that in the absence of functional SWI/SNF, the initiation of DNA end resection is significantly delayed. The delay in resection initiation is accompanied by impaired recruitment of MRX to the DSB, and other functions of MRX in HR including the recruitment of long-range resection factors and activation of the DNA damage response are also diminished. These phenotypes are correlated with a delay in the eviction of nucleosomes surrounding the DSB. We propose that SWI/SNF orchestrates the recruitment of a pool of MRX that is specifically dedicated to HR.